Pengembangan Modul Matematika Berbasis Pendidikan Rumah Dalam Pembelajaran Jarak Jauh Era Pandemi Covid-19 - Prastiwi, Aulia Anggi (Prosiding University Research Colloquium, 2021)
This study aims to: (1) develop the mathematics module home-based education in distance learning in the era of the covid-19 pandemic that can be used in learning (2) determine the feasibility of the module home education-based mathematics in pandemic era distance learning covid-19 based on an assessment by module experts, material experts, students and parents. This research is a type of module media development research which carried out at home using the Research and Development model Development (R&D) Borg and Gall which has been modified (Sugiyono, 2013:21) namely: exploring potentials and problems, data collection, product design, validation design, design revision, product trial, product revision, usage test, and revision product. The subjects involved in this study consisted of: 2 module media experts, 2 material experts, and 25 students and 25 parents of grade IV SD Negeri Gelangan 1 Magelang District, Central City, Magelang City. Method of collecting data done by using the method of observation, interviews, and questionnaires. Test the validity of the respondent's questionnaire using expert judgment (instrument) in consultation with experts). Prerequisite test of instrument analysis consists of test validity and reliability test. Data analysis using Likert scale. The results of this study indicate that: (1) math-based module home education in distance learning in the era of the covid-19 pandemic for classes IV SD has been developed through nine stages and can be used in learning. (2) home education-based mathematics module in distance learning in the era of the covid-19 pandemic for grade IV SD has been tested eligibility by experts, students and parents. Eligibility results by media experts module obtained a score of 3.8 with very good criteria, the feasibility of the module by material expert 3.2 with very good criteria, the feasibility of the module by students at the stage product trial (small scale) by 91% and parents at the product trial stage (small scale) by 88%, and students at the trial stage (large scale) by 96.20% and parents at the product trial stage (large scale) of 96.50%. The results of this study prove that the mathematics module based on home education in distance learning in the era of the covid-19 pandemic on the eyes Mathematics lessons for grade IV SD are suitable for use in learning.